Tracking pyrethroid resistance in arbovirus mosquito vectors: mutations I1532T and F1534C in Aedes albopictus across Europe - Pichler, Verena; Valadas, Vera; Akiner, Mustafa M; Balatsos, Georgios; Barceló, Carlos; Borg, Maria Louise; Bouyer, Jeremy; Bravo-Barriga, Daniel; Bueno, Ruben; Caputo, Beniamino; Collantes, Francisco; Delacour-Estrella, Sarah; et al. (My University, 2025)
With the worldwide spread of the Asian tiger mosquito, Aedes albopictus, the number of autochthonous cases of exotic arboviral diseases, such as dengue or chikungunya, is increasing in temperate regions. In Europe, pyrethroids are the only insecticides allowed for the abatement of adult mosquitoes and are thus crucial for limiting ongoing arbovirus transmission. Despite this and the report of resistance rising in vector populations worldwide, information on the pyrethroid resistance status of vector populations and knowledge on resistance mechanisms is widely lacking. Genotyping of knockdown resistance (kdr) mutations situated within the target site of pyrethroids, i.e., the voltage-gated sodium channel (VGSC), and associated with pyrethroid resistance, is a cost-effective approach to investigate the spread of resistance in a population. Herein, we describe the European-wide distribution of two kdr mutations, i.e., I1532T and F1534C, in Ae. albopictus and evaluate their co-occurrence with another well-characterized kdr mutation, V1016G.
Keywords: Aedes albopictus; Kdr; Arbovirus vector; Europe; Insecticide resistance; Vector control; Mosquito